2015
DOI: 10.1111/vop.12248
|View full text |Cite
|
Sign up to set email alerts
|

Normal bacterial conjunctival flora in theHuacaya alpaca (Vicugna pacos)

Abstract: Gram-positive aerobes were most commonly cultured, with S. xylosus and viridans streptococci predominating. To the best of the authors' knowledge, this is the first report describing the presence of Moraxella species in the healthy conjunctival sac of alpacas. Alpacas harboring viridans streptococci and Moraxella species were significantly younger.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…This study demonstrated the dominance of Gram-positive species in the conjunctival bacterial flora of normal Persian cats, which was in agreement with data previously reported for cats and other species. [4][5][6][7][10][11][12][19][20][21][22][23][24][25][26][27][28][29][30][31] Three studies reported on the normal conjunctival flora of cats in Canada, Poland, and Brazil. 7,9,12 In these D 7 9 3 studies, Gram-positive bacteria and specifically S0 epidermidis were reported as dominant conjunctival bacterial flora in cats.…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrated the dominance of Gram-positive species in the conjunctival bacterial flora of normal Persian cats, which was in agreement with data previously reported for cats and other species. [4][5][6][7][10][11][12][19][20][21][22][23][24][25][26][27][28][29][30][31] Three studies reported on the normal conjunctival flora of cats in Canada, Poland, and Brazil. 7,9,12 In these D 7 9 3 studies, Gram-positive bacteria and specifically S0 epidermidis were reported as dominant conjunctival bacterial flora in cats.…”
Section: Discussionmentioning
confidence: 99%
“…This microflora contributes to the normal ocular defence by maintaining the population balance and preventing overgrowth of potentially pathogenic agents (Lu & Liu 2016). Composition of the commensal conjunctival bacterial and fungal flora has been reported in numerous species, including horse, donkey, alpaca, cattle, dog and cat in different countries, revealing both inter-and intraspecies differences in prevalence (Samuelson et al 1984, Nardoni et al 2007, Voelter-Ratson et al 2013, Khosravi et al 2014, Kiełbowicz et al 2014, Verneuil et al 2014, Storms et al 2015. Commensal populations may vary in relation to contamination from the environment (geographic location, climate, season, feed and husbandry) (Andrew et al 2003, Kiełbowicz et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Many factors, such as season, geography, temperature, housing, as well as age, sex, and breed, are described to affect the frequency and composition of the microbiota of the ocular surface in horses, dogs, cats, and alpacas …”
Section: Introductionmentioning
confidence: 99%
“…affect the frequency and composition of the microbiota of the ocular surface in horses, dogs, cats, and alpacas. [8][9][10][11][12][13][14] In cats and in other domestic animals, Gram-positive bacteria predominate, but the prevalence rates vary for each species. It has been assumed that the conjunctival sac of cats is relatively sterile in contrast to dogs and horses.…”
mentioning
confidence: 99%